Nonlinear internal waves and plumes generated in response to sea‐loch outflow, AUV, and time‐lapse photography observations. Issue 7 (10th July 2017) - Toberman, Matthew; Inall, Mark; Boyd, Tim; Dumount, Estelle; Griffiths, Colin
Abstract: The tidally modulated outflow of brackish water from a sea loch forms a thin surface layer that propagates into the coastal ocean as a buoyant gravity current, transporting nutrients and sediments, as well as fresh water, heat and momentum. The fresh intrusion both propagates into and generates a strongly stratified environment which supports trains of nonlinear internal waves (NLIWs). NLIWs are shown to propagate ahead of this buoyancy input in response to propagation of the outflow water into the stratified environment generated by the previous release as well as in the opposing direction after the reflection from steep bathymetry. Oblique aerial photographs were taken and photogrammetric rectification led to the identification of the buoyant intrusion and the subsequent generation of NLIWs. An autonomous underwater vehicle (AUV) was deployed on repeated reciprocal transects in order to make simultaneous CTD, ADCP, and microstructure shear measurements of the evolution of these phenomena in conjunction with conventional mooring measurements. AUV‐based temperature and salinity signals of NLIWs of depression were observed together with increased turbulent kinetic energy dissipation rates of over 2 orders of magnitude within and in the wake of the NLIWs. Repeated measurements allow a unique opportunity to investigate the horizontal structure of these phenomena. Simple metric scaling demonstrates that these processes are likely to be feature of many fjordic systems located on the west coast of Scotland but may also play a key role in the assimilation of the outflow from many tidally dominated fjordic systems throughout the world. Key Points: Buoyant plumes and nonlinear internal waves are shown to be generated by, and in response to sea‐loch outflow These internal processes are shown to be turbulent and result in active mixing and the entrainment of fresh water into the coastal ocean Simple scaling demonstrates that these processes are likely to feature in many other fjordic systems both in Scotland and the rest of the world